PUBLIC RELATIONS STRATEGY THROUGH CORPORATE SOCIAL RESPONSIBILITY (CSR) IN PARTNERSHIP AND ENVIRONMENTAL DEVELOPMENT (PKBL) PROGRAM - Aeni, Dini Nur; Nurfalah, Farida; Bharoto, Haryo (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2022)
Forests are biological natural resources that have great benefits. Inside it. The research objectives include 1) Public Relations Strategy through Corporate Social Responsibility (CSR) in the Partnership and Community Development Program (PKBL) at Perum Perhutani KPH Majalengka 2) What are the Barriers to the Public Relations Strategy and 3) what are the efforts made by Public Relations in dealing with obstacles that happened. The researcher uses a qualitative descriptive research method, the selection of informants uses the Purpose Sampling Technique. The results of this study indicate that the implementation of the Public Relations Strategy through CSR in the Partnership and Community Development Program (PKBL) at Perum Perhutani KPH Majalengka has been implemented but in its implementation it has not been able to be carried out optimally. it can be seen from: 1). Public Relations Strategy through CSR in PKBL at Perum Perhutani KPH Majalengka that the community complains about solving problems that often arise to be reviewed and rechecked by Perhutani and the delivery of communications that have not been properly realized to stakeholders, 2). Barriers to the Public Relations Strategy through CSR in PKBL at Perum Perhutani KPH Majalengka there is a lack of good communication management in the form of miscommunication between work units in problem solving 3). Public Relations Strategy Efforts through CSR in PKBL at Perum Perhutani KPH Majalengka through meetings and coordinating with each other between work units as well as making agendas and reviewing them so that they are more focused in accordance with more mature planning.